Prolonged Postictal Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs, 1990)
Prolonged postictal confusion lasting from four to ten days is reported in 11 patients (ages 7½ to 40 years) from the Epilepsy Research Center, Department of Neurology, University of Minnesota and MINCEP Epilepsy Care, P.A., Minneapolis.